Software tools for creating interfaces for interaction with Arduino via Bluetooth - М. Kliuba; Т. Likhouzova (Adaptivni Sistemi Avtomatičnogo Upravlinnâ)
The article describes the problem of communication of microcontrollers of the AVR family with other Bluetooth devices using special modules. A comprehensive solution is proposed, including a modified interaction protocol, a library for Arduino that implements interaction on the microcontroller side, and a mobile application for creating interfaces that allows a user to interact with Arduino via Bluetooth. The development environment was chosen to be Android Studio together with the SDK tools (API 34). The Kotlin language and software tools from Android Jetpack, including Jetpack Compose, are used for programming, which allows you to create more flexible, efficient and attractive user interfaces for Android applications. A modification of the SPP protocol is used for data exchange between devices. To implement user interaction with the application on the Arduino side, the BluetoothMe library has been developed, which, using the IBluetoothAdapter interface, encapsulates work with the Bluetooth adapter and provides convenient functions for sending and receiving data. This approach allows the user to use any Arduino-compatible Bluetooth module. The development is aimed primarily at amateurs of robotics and microelectronics, but it will be useful for professionals as well. The proposed software allows developers to create more complex and powerful electronic devices in less time. This makes it possible to expand the boundaries of technical progress and ensures the creation of new, more efficient and powerful devices that can perform various tasks.